Intercalation and calcination as methods to reduce expansive soil properties - Ristiya Adi Wiratama (Sains Tanah: Journal of Soil Science and Agroclimatology, 2021)
The expansive ability of soil causes a series of problems in various sectors. The dominance of smectite clay minerals significantly affects expansive ability because they have an unstable interlayer structure. Cation intercalation and calcination is a treatment method that can increase the stability of the clay interlayer structure. This research investigated the effects of intercalation cations and calcination treatment on the swelling ability and cracking properties in the clay from vertisols; the cations used for intercalation were aluminum and iron. The intercalation tested doses were based on the equivalent weight of 0x, 0.5x, and 1x cation exchange capacity (CEC) clay value. The calcination treatments used were 200°C, 300°C, and no calcination. Each treatment interaction was repeated three times. Parameters observed were the total area, average crack width, average lump area, total number of lumps, moisture content, swelling volume, and pH after treatment. The results showed that each treatment had a significant effect. Clay with an Al intercalation dose of 1x CEC without calcination treatment had the highest total area after drying, which was 41.035 cm2; the lowest average crack width was 0.153 cm, and the smallest swelling volume was 3.6 cm3. In contrast, the clay without intercalation and calcination treatments had a swelling volume up to 10 cm3 on the 7th day. The clay with an Al intercalation dose of 1x CEC with 200°C calcination exhibited the best results in reducing the expansive clay ability and can be used as a guideline for further testing to reduce the soil’s expansive ability.